Synthesis of two new hydroximinosteroids from cholesterol and their biological evaluation - Ha, Dinh Thi; Salvaraja, Baskar; Long, Pham Quoc; Quang, Ngo Dai; Nghi, Do Huu; Wook, Lee Jae; Thuy, Tran Thi Thu (Vietnam Journal of Science and Technology, 2019)
A simple and efficient synthesis of two new hydroximinosteroidal derivatives (11, 13) from cholesterol was described. The cytotoxicity of these compounds, their intermediates were evaluated on human cancer cell lines including Hep-G2, HeLa and T98G. Compound 13 presented a potent antiproliferative effect to T98G cancer cell at 2.9 mM of IC50. In addition, the antimicrobial assay showed that two new oximes 11 and 13 were active against E. coli and S. aureus strain (MIC :50 mg/mL)